Penerapan Prinsip Mindful, Meaningful, Dan Joyful Learning Dalam Pembelajaran Deep Learning Di Mi Islamiyah Plosobuden - Rifdah Atikah; Siti Latifatus Sun’iyah; Zuli Dwi Rahmawati (Jurnal Pendidikan Rafflesia, 2026)
This study is motivated by the importance of the teacher's role in creating meaningful and deep learning experiences for students amid the demands of 21st-century education. The concept of deep learning, Deep learning-based instruction is considered to be am recognized as an effective approach to enhancing the quality of education because it promotes students' comprehensive understanding, active engagement in the learning process, and the development of spiritual and social values. This study aims to describe (1) the implementation of deep learning-based instruction, (2) the application of the mindful, meaningful, and joyful learning principles, and (3) the strengths and weaknesses of their implementation at MI Islamiyah Plosobuden. The study used a descriptive qualitative approach with a classroom action research (CAR) design. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing/verification. Data validity was examined through source, technique, and time triangulation. The results show that: (1) teachers planned learning through teaching modules containing trigger questions, learning objectives, and time allocation; (2) the implementation of learning integrated the three pillars of deep learning, namely connecting (mindful), experiencing (joyful and meaningful), and constructing meaning (meaningful and mindful); and (3) the evaluation indicated positive feedback and contributed to the effectiveness of learning at MI Islamiyah Plosobuden, although challenges remained in the form of differing student abilities and limited time and facilities.